Penerapan Metode PIECES Framework Pada Tingkat Kepuasan Sistem Informasi Layanan Aplikasi Myindihome - Ngakan Made Bayu Aditya; Joy Nashar Utama Jaya (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
The development of information systems and information technology, of course, can also change people's behavior in carrying out their activities, which were originally done manually, now they can be done digitally so that they are more effective and efficient. Customer satisfaction is a person's level of feeling after being able to compare the perceived performance or results compared to their expectations. Indihome is one of the products of PT. Telkom as a provider of Indihome service products which has services in the form of mobile application-based services, namely Myindihome. The PIECES framework is a framework that has six categories in classification and problem solving, namely Performance, Information and Data, Economics, Control and Security, Efficiency, and Service. This study uses the PIECES Framework method in analyzing data, the use of the PIECES framework method is very suitable in analyzing each system variable being studied because it can provide real results on the effectiveness of the system used by the company. Customer satisfaction with mobile application-based services is measured by the PIECES framework to determine the level of customer satisfaction with services. In this study, measurements were carried out using the PIECES Framework, resulting in an average score of 4.26 with a Likert scale. So service users are categorized as satisfied with mobile-based information system services.